Mental Health Screening: Relevance of The VPI and The GHQ - Doondy Abhay Malladi; Geetha Srinivas (Journal of Psychology and Social Sciences, 2026)
This study, embodies a holistic approach and a qualitative thematic approach to the rising concerns towards the depleting mental health in Indian working population. Mental health screening is often, silhouette by the Western Diagnostic paradigms. This results in the under-utilization of the culturally specific representations, which is the research gap that is represented through this qualitative paper.  This paper implores and explores the lens, Indian Knowledge System (IKS) which is an initiative under the Ministry of Education MoE, deeply rooted in Yoga, Ayurveda, and Meditation. Simultaneously, studying its utility, as well as integrating with contemporary mental health diagnosis the General Health Questionnaire (GHQ), emphasizing its relevance for the working population facing diverse psychological challenges. The Vedic Personality Inventory (VPI) is framework that is deeply engrained in ancient Indian texts such as the Rig Veda, Yajur Veda, Sama Veda, Atharva Veda, and Upanishads, serves as a paradigm to screen mental health or condition of an individual’s consciousness by assessing personality traits linked to mental health. This study imparts the General Mental Health Questionnaire (GHQ) developed by David Goldberg, which screens using 4 areas, A, B, C and D, stress, anxiety, social dysfunction and somatic symptoms, respectively. Concerning the increase in mental health trauma among the working population, this research posits that through the lens of IKS i.e. using the VPI in integration with the GHQ. This interdisciplinary approach addresses existing research gaps in culturally contextual mental health assessment tools, advocating the revitalization of traditional knowledge in modern psychological practice.